Diurnally resolved particulate and VOC measurements at a rural site: indication of significant biogenic secondary organic aerosol formation - S. J. Sjostedt; J. G. Slowik; J. R. Brook; R. Y.-W. Chang; C. Mihele; C. A. Stroud; A. Vlasenko; J. P. D. Abbatt (Atmospheric Chemistry and Physics, 2011)
We report simultaneous measurements of volatile organic compound (VOC) mixing ratios including C6 to C8 aromatics, isoprene, monoterpenes, acetone and organic aerosol mass loadings at a rural location in southwestern Ontario, Canada by Proton-Transfer-Reaction Mass Spectrometry (PTR-MS) and Aerosol Mass Spectrometry (AMS), respectively. During the three-week-long Border Air Quality and Meteorology Study in June–July 2007, air was sampled from a range of sources, including aged air from the polluted US Midwest, direct outflow from Detroit 50 km away, and clean air with higher biogenic input. After normalization to the diurnal profile of CO, a long-lived tracer, diurnal analyses show clear photochemical loss of reactive aromatics and production of oxygenated VOCs and secondary organic aerosol (SOA) during the daytime. Biogenic VOC mixing ratios increase during the daytime in accord with their light- and temperature-dependent sources. Long-lived species, such as hydrocarbon-like organic aerosol and benzene show little to no photochemical reactivity on this timescale. From the normalized diurnal profiles of VOCs, an estimate of OH concentrations during the daytime, measured O3 concentrations, and laboratory SOA yields, we calculate integrated local organic aerosol production amounts associated with each measured SOA precursor. Under the assumption that biogenic precursors are uniformly distributed across the southwestern Ontario location, we conclude that such precursors contribute significantly to the total amount of SOA formation, even during the period of Detroit outflow. The importance of aromatic precursors is more difficult to assess given that their sources are likely to be localized and thus of variable impact at the sampling location.